2013
DOI: 10.1002/grl.50178
|View full text |Cite
|
Sign up to set email alerts
|

Glacier tongue calving reduced dense water formation and enhanced carbon uptake

Abstract: [1] Dense shelf water formed in the Mertz Polynya supplies the lower limb of the global overturning circulation, ventilating the abyssal Indian and Pacific Oceans. Calving of the Mertz Glacier Tongue (MGT) in February 2010 altered the regional distribution of ice and reduced the size and activity of the polynya. The salinity and density of dense shelf water declined abruptly after calving, consistent with a reduction of sea ice formation in the polynya. Breakout and melt of thick multiyear sea ice released by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
117
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(123 citation statements)
references
References 48 publications
(52 reference statements)
5
117
1
Order By: Relevance
“…In 2005, when the abovedescribed pattern was particularly conspicuous, high Chl a (up to 20 µg L −1 ) in the southern coastal area of the sampling grid provides further evidence that high primary productivity led to the observed high arag despite the presence of freshwater. Similar results were found after the calving event of the Mertz Glacier tongue in eastern Antarctica, where enhanced primary productivity increased the arag and thereby counteracted the effect of dilution by meltwater input (Shadwick et al, 2013).…”
Section: Parametersupporting
confidence: 78%
“…In 2005, when the abovedescribed pattern was particularly conspicuous, high Chl a (up to 20 µg L −1 ) in the southern coastal area of the sampling grid provides further evidence that high primary productivity led to the observed high arag despite the presence of freshwater. Similar results were found after the calving event of the Mertz Glacier tongue in eastern Antarctica, where enhanced primary productivity increased the arag and thereby counteracted the effect of dilution by meltwater input (Shadwick et al, 2013).…”
Section: Parametersupporting
confidence: 78%
“…Shadwick et al [2013] link the freshening of 0.15 of the dense shelf water observed in the Ad elie Depression between 2008 and 2011 to reduced sea ice production in the reshaped MGP after the Mertz Glacier calving. Studying the impact of the glacier calving on ice production in the MGP, Tamura et al [2012] indeed found that annual sea ice production in the polynya extending over the Ad elie Depression and the Mertz Depression had reduced by 14% and 20% in 2010 and 2011, respectively, out of an annual mean of approximately 170 km 3 estimated over the precalving period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009).…”
Section: Introductionmentioning
confidence: 90%
“…Glacial melt may arise from enhanced contact of land or sea ice with relatively warm water, especially with the Modified Circumpolar Deep Water (MCDW) intruding on the shelf. Although there is no evidence that such a process did impact on the dense shelf water freshening observed in summer 2011 in the Ad elie Depression, Shadwick et al [2013] suggest that it may have contributed to the 1.16 m excess of freshwater added to the top 200 m of the Ad elie Depression in that year, as a result of more ice being advected and melted into the region after the removal of the Mertz ''barrier.'' With regards to dense water production, surface freshening increases the upper ocean vertical stability which in late summer-fall may alter preconditioning of the water column with regards to the following winter convection.…”
Section: Introductionmentioning
confidence: 99%
“…For more details on the study area and the oceanography we refer to numerous papers on the region (e.g. Beaman and Harris, 2005;Cougnon et al, 2013Cougnon et al, , 2017Shadwick et al, 2013;Kusahara et al, 2017;Jansen et al, 2018).…”
Section: Study Areamentioning
confidence: 99%
“…The calving of the Mertz Glacier Tongue (MGT) in 2010 (Young et al, 2010) has resulted in profound environmental changes in the region, such as increased sea-ice concentrations (Campagne et al, 2015), and changes in ocean currents along the shelf as suggested by observations and modeling studies (Cougnon et al, 2017;Kusahara et al, 2017). These environmental changes have consequences for the dynamics and distribution of primary production (Shadwick et al, 2013), the abundance of top-predators (Wilson et al, 2016), and has been observed to influence the community structure of shallow-water benthos (Clark et al, 2015). However, the effect of the MGT-calving on the seafloor across the region has so far neither been assessed nor observed, and so its impact on benthic communities across the continental shelf is still unknown.…”
Section: Introductionmentioning
confidence: 99%